Role Play and Speaking Achievement of the Tenth Graders Based on Self Concept, Gender, and Grammar Mastery - Rizqy Khairunnisa; Chuzaimah D. Diem; Soni Mirizon (LINGUA: Jurnal Bahasa dan Sastra, 2018)
Abstract: Role Play is an interesting strategy which gives a great benefit for many students. It can be used to encourage general oral fluency or to train students’ speaking for specific situation. The objectives of this study were to find out whether or not there were significant interaction effects of Role Play and self-concept, gender, and grammar mastery on the tenth graders’ speaking achievement. Factorial design was used in this study which involved two groups (experimental and control groups). Forty students were selected as the sample of this study and equally divided into experimental and control groups. The result showed that the experimental group had better improvement in speaking achievement than the control group which did not get any treatment using Role Play. However, there were no interaction effects between Role Play Technique and Self Concept, Gender, Grammar Mastery on the students’ speaking achievement.Keywords: role play, speaking achievement, gender, self-concept, grammar masteryAbstrak: Role play adalah strategi yang menarik yang memberikan manfaat besar bagi banyak siswa. Role Play dapat digunakan untuk mendorong kefasihan secara umum atau untuk melatih siswa berkomunikasi dalam situasi yang lebih spesifik. Tujuan dari penelitian ini adalah untuk mengetahui ada atau tidaknya pengaruh interaksi yang signifikan antara role play dan konsep diri, gender, dan penguasaan tata bahasa terhadap pencapaian berbicara siswa kelas sepuluh. Penelitian ini menggunakan desain faktorial yang melibatkan empat puluh siswa dan dibagi ke dalam kelompok eksperimen dan kontrol. Hasilnya menunjukkan bahwa kelompok eksperimen mengalami peningkatan yang lebih baik dalam hal berbicara dari pada kelompok kontrol. Na- mun tidak ada efek interaksi antara tekhnik role play dan konsep diri, gender, dan penguasaan tata bahasa terhadap pencapaian berbicara siswa. Kata-kata Kunci: bermain peran, pencapaian berbicara, jenis kelamin, konsep diri, pengua- saam tata bahasa